Analysis Of The Value Of Character Education In The Fable Of The Mouse Deer and His Best Friend - Nurmila Wati; Dhiniaty Gularso (Universitas PGRI Yogyakarta, 2022)
This research aims to 1) know the values of the characters in the Fable of the Mouse Deer and his best friends. 2) find out the relevance of the character values in the fable book mousedeer and his best friend with the character values applied in elementary school. The research was conducted using the literature study method or literature of secondary data sources collected through textbooks, e-books, scientific journals, and educational journals. The stages of the data validity test consisted of collecting data or secondary sources, source criticism carried out by validators, interpretation or analysis of data, and historiography or writing of research results, then conclusions were drawn based on data analysis and research results. The results showed that 1) the fable text in the Fable book entitled mousedeer and his close friends contained character values namely the values of independent, creative, tolerance, friendly, environmental care, social care, hard work, peace-loving, democratic, religious. 2) the character values were in accordance with the 2013 curriculum include core competencies -1 (Ki-1) religious attitudes, core competencies -2 (Ki-2) social attitudes. The character values in children's story books of Fable entitled Mousedeer and his Best Friends were relevant to the regulation of the President of the Republic of Indonesia Number 87 of 2017. The character education values were formulated into 18, i.e.: religious, honest, tolerance, discipline, hard work, creative, independent, democratic, curiosity, spirit of nationalism, love for the homeland, respect for achievement, friendly/communicative, love peace, love to read, care for the environment, care about social, and responsibility.